The sRNA Regulated Protein DdbA Is Involved in Development and Maintenance of the Chlamydia trachomatis EB Cell Form - Grieshaber, Nicole A.; Runac, Justin; Turner, Sierra; Dean, Marissa; Appa, Cody; Omsland, Anders; Grieshaber, Scott S. (Frontiers in Cellular and Infection Microbiology, 2021)
The chlamydial small non coding RNA, IhtA, regulates the expression of both HctA and DdbA, the uncharacterized product of the C. trachomatis L2 CTL0322 gene. HctA is a small, highly basic, DNA binding protein that is expressed late in development and mediates the condensation of the genome during RB to EB differentiation. DdbA is conserved throughout the chlamydial lineage, and is predicted to express a small, basic, cytoplasmic protein. As it is common for sRNAs to regulate multiple mRNAs within the same physiological pathway, we hypothesize that DdbA, like HctA, is involved in regulating RB to EB differentiation. Here, we show that DdbA is a DNA binding protein, however unlike HctA, DdbA does not contribute to genome condensation but instead has endonuclease activity. Using a DdbA temperature sensitive mutant, we show that DdbAts creates inclusions indistinguishable from WT L2 in size and that early RB replication is likewise similar at the nonpermissive temperature. However, the number of DdbAts infectious progeny is dramatically lower than L2 overall, although production of EBs is initiated at a similar time. The expression of a late gene reporter construct followed live at 40ºC indicates that late gene expression is severely compromised in the DdbAts strain. Viability assays, both in host cells and in axenic media indicate that the DdbAts strain is defective in EB maintenance. Additionally, using Whole Genome Sequencing we demonstrate that chromosome condensation is temporally separated from DNA replication during the RB to EB transition. Although DdbA does not appear to be directly involved in this process, our data suggest it is a DNA binding protein that is important in the production and maintenance of infectivity of the EB, perhaps by contributing to the remodeling of the EB chromosome.